PENGARUH PENERAPAN KURIKULUM MERDEKA TERHADAP MOTIVASI BELAJAR SISWA DI SDN 27 LADANG HUTAN - Sadria Idaman; Bambang Trisno; Nelfanita Nelfanita (ADIBA : JOURNAL OF EDUCATION, 2024)
This research aims to determine the relationship between increasing student learning motivation by implementing the independent learning curriculum at SDN 27 Ladang Hutan. The type of research used is qualitative research, the objects of research are the principal, teachers and students at Sdn 27 Ladang Hutan. Data collection is used through interviews, observations, questionnaires and library studies. Data analysis techniques use SWOT analysis techniques. Identifying internal and external factors is a stage that must be passed through interviews using the IFE matrix, EFE matrix, SWOT matrix and finally using score weight table analysis. Where there is high encouragement in learning and students are willing to provide enough time to study so that students are able to increase learning motivation in implementing the independent curriculum, the level of student motivation in learning will increase well and make it easier to implement the independent learning curriculum.